'Scalping' of albatross fledglings by introduced mice spreads rapidly at Marion Island. Issue 2 (2nd November 2015) - Dilley, Ben J.; Schoombie, Stefan; Schoombie, Janine; Ryan, Peter G.
Abstract: House mice ( Mus musculus L.) were introduced to sub-Antarctic Marion Island more than two centuries ago, and have been the only introduced mammal on the island since 1991 when feral cats were eradicated. The first mouse-injured wandering albatross ( Diomedea exulans L.) chick was found in 2003 and since then attacks have continued at a low level affecting <1% of the population. In 2009, the first 'scalpings' were detected; sooty albatross ( Phoebetria fusca Hilsenberg) fledglings were found with raw wounds on the nape. In 2015, mice attacked large chicks of all three albatross species that fledge in autumn: grey-headed ( Thalassarche chrysostoma Forster) (at least 102 wounded chicks; 4.6% of fledglings), sooty ( n =45, 4.3%) and light-mantled albatross ( P. palpebrata Forster) ( n =1, 4%). Filming at night confirmed that mice were responsible for wounds. Attacks started independently in small pockets all around the island's 70 km coastline, separated by distances hundreds of times greater than mouse home ranges. The widespread nature of mouse attacks in 2015 on large, well-feathered chicks is alarming and highlights not only Marion Island as a priority island for mouse eradication but also that mice alone may significantly affect threatened seabird species.